Secondary resection tracheal was facilitated in robot-assisted left pneumonectomy - Duan, Hongtao (J Thorac Dis, 2018)
The purpose of the essay is to introduce a new procedure in term of robot-assisted left pneumonectomy. The “secondary resection tracheal” technique is that, the left bronchi, which was 3–4 cm apart from trachea carina was disserted firstly, as the distal bronchi stump was lifted, with more space and vision being explored, the artery was pinned down easily, chipped and cut accurately. As far as the program goes down, it is more privileged but one point where it was capable of avoiding or decreasing the risk of ripping the left artery. In addition to isolating, lifting or tracting the proximal tracheal stump, the endo-GIA staple was much easier used to cut the tracheal stump secondly and to deliver shorter one as well as to reduce the odds of the bronchial stump fistula. Moreover, for the preliminary date has indicated, there’s been a significant decrease in intraoperative hemorrhage involving with the left pneumonectomy.